Penguatan Kapasitas Kelembagaan Kelompok PEW untuk Pengembangan Ekonomi Lokal Kota Yogyakarta - Yuli Kurniyati (Jurnal Maksipreneur, 2013)
The purpose of this study was to analyze institutional capacity the PEW Group Members, and analyzing institutional performance, and formulate strategies and institutional capacity building programs in the PEW Group of local economic development in the city of Yogyakarta. The method used in this study is a qualitative method. Data collection techniques used are: observation, documentation studies, in-depth interviews, and questionnaires. Assessment strategies in the analysis of this problem using the Logical Framework Analysis . Repayment rates in Sub Pringgokusuman PEW group 76% (25 groups) are classified as current, 12% classified as substandard, and there are 4 groups (12%) were classified as jammed. Judging from the direction of development of the group based on the performance aspects of the organization, administration, financing, production and rooting business. There are 18 (54.55%) groups were included in the growth category, and 15 (45.45%) group included in the category of development, while the group in the category are not independent. Formulation of institutional capacity strengthening program group includes: 1) Improvement Skills Productive Economic Business Members, 2) Strengthening Institutions Norm, 3) Administrative Arrangement group, and 4) Increased Capital to expand cooperative network.